Learnings from Conducting an Online Lesson Study for the Online Teaching of Radian Measure - Flores, Leroy A.; Presto, Adaiah C.; Combo, John Edward A.; Caballero, Jaime G.; Palanas, Victorina D.; Devis, Rolly A.; Elipane, Levi E. (Future Science / FSH-PH Publications, 2022)
With the shift of learning modality from face-to-face to online distance learning, teaching Mathematics has been linked to new challenges and constraints. This paper investigates how radian measure can be taught via distance learning delivery modality. An Online Lesson Study was conducted, and the research lesson was implemented for first-year college students taking Bachelor of Secondary Education major in Mathematics at a state university in the Philippines. The recorded dialogues during the post-lesson discussion were transcribed and analyzed by the researchers. Through these processes, three themes emerged: (1) logistical issues in online teaching, (2) alignment of purpose and approach in online teaching, and (3) theoretical underpinnings for online teaching. Hence, online lesson study provides a venue for teachers to pursue professional development amidst the pandemic.